A method for improving the stability of solid electrolyte slurry products and slurry products

By adding lithium-containing salts to the solid electrolyte slurry, changing the isoelectric point of the particles and enhancing the electrostatic repulsion, the stability problems of the solid electrolyte slurry are solved, achieving better stability and longer storage time.

CN114421022BActive Publication Date: 2025-02-18JIANGSU LIONG0 NEW ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210049528.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-17
Publication Date
2025-02-18
Estimated Expiration
2042-01-17

AI Technical Summary

Technical Problem

There are stability problems in solid electrolyte slurry in terms of physical stability, chemical stability, electrochemical stability and interface stability during transportation, storage and use, and existing dispersants cannot effectively solve these problems.

Method used

Add lithium-containing salts to the solid electrolyte slurry as electrolyte dispersant to change the isoelectric point of the solid electrolyte powder particles, so that the zeta potential of the dispersion system deviates from the potential near the powder itself isoelectric point, and enhances the powder particles. The electrostatic repulsion force stabilizes the dispersion of powder particles.

Benefits of technology

It effectively improves the physical stability, chemical stability, electrochemical stability and interface stability of solid electrolyte slurry, extends the storage time of the product, and meets the stability requirements during transportation, storage and use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for improving the stability of a solid electrolyte slurry product and a slurry product. The method comprises: adding a lithium-containing salt to the solid electrolyte slurry; the lithium-containing salt is added to the slurry product as an electrolyte dispersant to change the isoelectric point of solid electrolyte powder particles in the solid electrolyte slurry product, so that the zeta potential of the dispersion system deviates from the potential near the isoelectric point of the powder itself, so that the electrostatic repulsion between the powder particles is greater than the van der Waals attraction, so that the powder particles are stably dispersed in the solid electrolyte slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material technology, and in particular to a method for improving the stability of a solid electrolyte slurry product and a slurry product. Background Art

[0002] The electrolyte of traditional lithium-ion batteries is liquid electrolyte, which has a series of safety hazards such as easy leakage, poor thermal stability, and easy fire and explosion once the battery is short-circuited. Compared with traditional liquid electrolytes, solid electrolytes have the advantages of high safety, high energy density, good cycle performance, wide operating temperature range, and convenient recycling. Solid electrolyte lithium-ion batteries are one of the research hotspots in the field of energy storage today.

[0003] Solid electrolytes are mainly divided into inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes. The large-scale production of inorganic solid electrolytes mostly adopts solid-phase sintering or hydrothermal method to prepare crude products. The crude products are made into slurry or powder after primary crushing and secondary sand grinding. Dry powders are easy to agglomerate and difficult to make into nanoscale. They can be dispersed in solvents to make nanoscale slurries. Slurries can be divided into water-based slurries and oil-based slurries. There are some stability problems in the transportation, storage and use of solid electrolyte slurries.

[0004] At present, the practical application of solid-state electrolytes is in the laboratory research and development stage. There is only gram-level supply of solid-state electrolyte powder on the market, and ton-level supply of solid-state electrolytes and their slurries is rare, so there is even less research on the stability of solid-state electrolyte slurries.

[0005] In the industry, the commonly used technical means to improve the physical stability of solid electrolyte slurry particle sedimentation is to add dispersants into the slurry to improve the surface activity of the particles and improve the physical stability of particle sedimentation.

[0006] However, the stability problems of solid electrolyte slurries, including physical stability, chemical stability, electrochemical stability, and interface stability, specifically including a series of problems such as surface tension, surface Gibbs free energy, interface chemistry, and interface electrochemistry, cannot be solved well by the dispersants currently used.

[0007] Because, although the commonly used dispersants are generally surfactants, the monomers formed by their dissolution are adsorbed on the surface of the solute particles to form a steric stabilization layer, thereby hindering the contact between the particles, preventing the particles from agglomerating and improving the physical stability. However, they cannot solve the problems of chemical stability, electrochemical stability, and interface stability, and dispersants will introduce other surface groups and impurity elements. Summary of the invention

[0008] To this end, the embodiments of the present invention provide a method for improving the stability of a solid electrolyte slurry product and a slurry product, which can effectively improve the physical stability, chemical stability, electrochemical stability, and interface stability of the solid electrolyte slurry.

[0009] In a first aspect, an embodiment of the present invention provides a method for improving the stability of a solid electrolyte slurry product, the method comprising: adding a lithium-containing salt to the solid electrolyte slurry;

[0010] The lithium-containing salt is added to the slurry product as an electrolyte dispersant to change the isoelectric point of the solid electrolyte powder particles in the solid electrolyte slurry product, so that the zeta potential of the dispersion system deviates from the potential near the isoelectric point of the powder itself, and the electrostatic repulsion between the powder particles is greater than the van der Waals attraction, thereby stably dispersing them in the solid electrolyte slurry.

[0011] Preferably, the solid electrolyte slurry comprises a solid electrolyte and a solvent; the solvent is water or a non-aqueous solvent containing trace amounts of water;

[0012] Under the condition that the solvent is water, the lithium-containing salt and water generate a trace amount of acid to reduce or remove the residual alkali on the surface of the solid electrolyte and lower the pH value of the solid electrolyte slurry; or,

[0013] Under the condition that the solvent is a non-aqueous solvent with trace water, the lithium-containing salt and the trace water generate trace acid to reduce or remove the residual alkali on the surface of the solid electrolyte and lower the pH value of the solid electrolyte slurry.

[0014] Further preferably, the lithium-containing salt added to the solid electrolyte slurry is used to increase the concentration of lithium ions in the solid electrolyte slurry and reduce the Li + / H + Proton exchange reaction improves the stability of solid electrolyte slurry.

[0015] Preferably, the step of adding a lithium-containing salt to the solid electrolyte slurry specifically includes:

[0016] The lithium-containing salt is added when the solid electrolyte particles are mixed with the solvent, and the mixture is circulated and sand-milled in a sand mill circulation tank to obtain a solid electrolyte slurry product.

[0017] Preferably, the step of adding a lithium-containing salt to the solid electrolyte slurry specifically includes:

[0018] The solid electrolyte particles are mixed with the solvent in proportion, and cyclically sand-milled and nano-sized in a sand mill circulation tank, and the lithium-containing salt is added during the cyclic sand-milling process to obtain a solid electrolyte slurry product.

[0019] Preferably, the step of adding a lithium-containing salt to the solid electrolyte slurry specifically includes:

[0020] The solid electrolyte particles and the solvent are mixed in proportion, and cyclically sand-milled and nano-milled in a sand mill circulation tank, and when the particle size of the solid electrolyte particles reaches a set size range, a solid electrolyte slurry is obtained;

[0021] The lithium-containing salt is added to the solid electrolyte slurry while continuously stirring the solid electrolyte slurry to obtain a solid electrolyte slurry product.

[0022] Preferably, the solid electrolyte comprises:

[0023] NASICON-type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3; wherein A is one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu or Y; B is one or more of Ti, Ge, Zr, Hf or Sn; 0≤x≤0.5; or,

[0024] Garnet-type oxide solid electrolyte Li x A3B2O 12 ; wherein A is one or more of La, Nb, Mg, Ba, Ca or Sr, B is one or more of Te, Ta, Nb, Zr or In, 0 <x≤7; or,

[0025] Perovskite-type oxide solid-state electrolysis of Li 3x La 2 / 3-x TiO3, 0<x≤2 / 3; or

[0026] Anti-perovskite oxide solid electrolyte Li3OX, Li 3-2x A x BO, Li 1.9 OHCl 0.9 or Li2OHCl; wherein X is Cl and / or Br; A is Mg 2+ , Ca 2+ , Sr 2+ Or Ba 2+ One or more of, B is Cl and / or I, 0≤x<3 / 2; or,

[0027] Thio-LISICON type sulfide solid electrolyte (100-x) Li2S-xP2S5 or Li 4-y A 1-y B yS4 or Li4SnS4; wherein 0<x<100; A is Ge and / or Si, B is one or more of P, Al or Zn, 0<y<1; or,

[0028] Li 11-x M 2-x P 1+x S 12 Type sulfide solid electrolyte, wherein M is at least one of Ge, Sn or Si, and 0≤x≤1;

[0029] Argentum-type sulfide solid electrolyte Li6PS5X; wherein X is at least one of Cl, Br, and I;

[0030] A halide solid electrolyte A3MX6; wherein A is at least one of Li or Na, M is at least one of trivalent metals In, Y, Er, Sc, and Zr, and X is at least one of Cl, Br, and I;

[0031] The non-aqueous solvent includes: N-methylpyrrolidone, methanol, ethanol, acetone, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, C n H 2n+2 , C n H 2n , one or more of petroleum ether, cyclohexane, carbon tetrachloride, trichloroethylene, carbon disulfide, toluene, benzene, dichloromethane, chloroform, ether, ethyl acetate, and acetone; wherein 5≤n≤12;

[0032] The lithium-containing salt includes: lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium difluorophosphate, lithium dioxalate borate, lithium difluorooxalate borate, bis(trifluoromethylsulfonyl imide) lithium, bis(fluorosulfonyl imide) lithium, difluorodioxalate lithium phosphate, lithium trifluoromethylsulfonate, (fluorosulfonyl) (perfluorobutylsulfonyl) imide lithium, bis(pentafluoroethylsulfonyl) imide lithium, bis(fluoromalonate) borate lithium, bis(2-methyl-2-fluoromalonate) borate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, lithium citrate, lithium acetate, lithium oxalate, lithium acetate, lithium borate, lithium perchlorate, lithium chlorate, lithium nitrate, lithium iodate, lithium bromate, lithium hexafluorosilicate, lithium silicate, lithium sulfate or lithium phosphate.

[0033] Further preferably, the Li 11-x M 2-x P 1+x S 12 The sulfide solid electrolytes specifically include: Li 10 GeP2S 12 or Li 10 SnP2S 12 or Li9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 .

[0034] Preferably, in the solid electrolyte slurry product, the content of lithium-containing salt is 0.01 mol / L-2.0 mol / L; the content of solid electrolyte is 1 wt%-80 wt%.

[0035] In a second aspect, an embodiment of the present invention provides a solid electrolyte slurry product obtained by using the method for improving the stability of a solid electrolyte slurry product described in the first aspect.

[0036] The method for improving the stability of a solid electrolyte slurry product proposed in the present invention is to add a lithium-containing salt to the slurry product as an electrolyte dispersant, change the isoelectric point of the solid electrolyte powder particles in the solid electrolyte slurry product, make the zeta potential of the dispersion system deviate from the potential near the isoelectric point of the powder itself, make the electrostatic repulsion between the powder particles greater than the van der Waals attraction, and thus stably disperse in the solid electrolyte slurry; and, by generating a trace acid through the lithium-containing salt and the water in the solvent, the surface residual alkali of the solid electrolyte can be reduced or removed, and the pH value of the solid electrolyte slurry can be reduced, which can solve the problem in the prior art that the slurry is alkaline due to the presence of LiOH and Li2CO3 on the surface of the solid electrolyte, which not only affects the transmission of lithium ions and has a large interface impedance, but also causes a gel jelly phenomenon when used with polyvinylidene fluoride (PVDF); thirdly, because the distribution of elements in the solid electrolyte is not completely uniform, there will be a gradient difference of lithium ions, and there will be Li on the surface of the solid electrolyte particles in the slurry. + / H + Proton exchange reaction, and by adding lithium-containing salt to the solid electrolyte slurry, the concentration of lithium ions in the solid electrolyte slurry can be increased and the Li + / H + Proton exchange reaction further improves the stability of the solid electrolyte slurry.

[0037] Therefore, the solid electrolyte slurry product obtained by the method has good storage stability, and as a slurry product, it can meet the requirements for stability during transportation, storage and use. At the same time, it also effectively prolongs the storage time of the product. DETAILED DESCRIPTION

[0038] The present invention will be further described below through specific examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0039] The present invention proposes a method for improving the stability of a solid electrolyte slurry product by adding a lithium-containing salt to the solid electrolyte slurry to improve the stability of the solid electrolyte slurry product. The specific implementation methods may include but are not limited to the following three methods:

[0040] The first method is to add lithium-containing salt when mixing solid electrolyte particles with solvent, and perform cyclic sand milling and nano-crystallization in a sand mill circulation tank to obtain a solid electrolyte slurry product.

[0041] The second method is to mix the solid electrolyte particles and the solvent in proportion, perform cyclic sand milling and nano-crystallization in a sand mill circulation tank, and add lithium-containing salt during the cyclic sand milling process to obtain a solid electrolyte slurry product.

[0042] The third method is to mix the solid electrolyte particles and the solvent in proportion, and perform cyclic sand milling and nano-crystallization in a sand mill circulation tank. When the particle size of the solid electrolyte particles reaches a set size range, a solid electrolyte slurry is obtained; and a lithium-containing salt is added under the condition of continuous stirring of the solid electrolyte slurry to obtain a solid electrolyte slurry product.

[0043] The solid electrolyte slurry includes a solid electrolyte and a solvent.

[0044] Among them, the solid electrolytes that can be used in the method of the present invention include but are not limited to:

[0045] NASICON-type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3; wherein A is one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu or Y; B is one or more of Ti, Ge, Zr, Hf or Sn; 0≤x≤0.5; or,

[0046] Garnet-type oxide solid electrolyte Li x A3B2O 12 ; wherein A is one or more of La, Nb, Mg, Ba, Ca or Sr, B is one or more of Te, Ta, Nb, Zr or In, 0 <x≤7; or,

[0047] Perovskite-type oxide solid-state electrolysis of Li 3x La 2 / 3-x TiO3, 0<x≤2 / 3; or

[0048] Anti-perovskite oxide solid electrolyte Li3OX, Li 3-2x A x BO, Li 1.9 OHCl 0.9or Li2OHCl; wherein X is Cl and / or Br; A is Mg 2+ , Ca 2+ , Sr 2+ Or Ba 2+ One or more of, B is Cl and / or I, 0≤x<3 / 2; or,

[0049] Thio-LISICON type sulfide solid electrolyte (100-x) Li2S-xP2S5 or Li 4-y A 1-y B y S4 or Li4SnS4; wherein 0<x<100; A is Ge and / or Si, B is one or more of P, Al or Zn, 0<y<1; or,

[0050] Li 11-x M 2-x P 1+x S 12 Type sulfide solid electrolyte, wherein M is at least one of Ge, Sn or Si, 0≤x≤1; specifically, it may include: Li 10 GeP2S 12 or Li 10 SnP2S 12 or Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 ;

[0051] Argentum-type sulfide solid electrolyte Li6PS5X; wherein X is at least one of Cl, Br, and I;

[0052] Halide solid electrolyte A3MX6; wherein A is at least one of Li or Na, M is at least one of trivalent metals In, Y, Er, Sc, and Zr, and X is at least one of Cl, Br, and I.

[0053] The solvent is water or a non-aqueous solvent containing trace amounts of water; the non-aqueous solvents include: N-methylpyrrolidone, methanol, ethanol, acetone, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, C n H 2n+2 , C n H 2n , one or more of petroleum ether, cyclohexane, carbon tetrachloride, trichloroethylene, carbon disulfide, toluene, benzene, dichloromethane, chloroform, ether, ethyl acetate, and acetone; among which, 5≤n≤12.

[0054] Lithium-containing salts include, but are not limited to, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorobisoxalate phosphate, lithium trifluoromethylsulfonate, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(fluoromalonate)borate, lithium bis(2-methyl-2-fluoromalonate)borate, lithium 4,5-dicyano-2-trifluoromethyl-imidazole, lithium citrate, lithium acetate, lithium oxalate, lithium acetate, lithium borate, lithium perchlorate, lithium chlorate, lithium nitrate, lithium iodate, lithium bromate, lithium hexafluorosilicate, lithium silicate, lithium sulfate or lithium phosphate.

[0055] In the solid electrolyte slurry product formed by the present invention, the content of the lithium-containing salt is 0.01 mol / L-2.0 mol / L; the content of the solid electrolyte is 1 wt%-80 wt%.

[0056] The method for improving the stability of a solid electrolyte slurry product proposed in the present invention is to add a lithium-containing salt into the slurry product as an electrolyte dispersant, change the isoelectric point of the solid electrolyte powder particles in the solid electrolyte slurry product, make the zeta potential of the dispersion system deviate from the potential near the isoelectric point of the powder itself, make the electrostatic repulsion between the powder particles greater than the van der Waals attraction, and thus stably disperse in the solid electrolyte slurry; and, by generating a trace acid through the lithium-containing salt and the water in the solvent, the surface residual alkali of the solid electrolyte can be reduced or removed, and the pH value of the solid electrolyte slurry can be reduced, which can solve the problem in the prior art that the slurry is alkaline due to the presence of LiOH and Li2CO3 on the surface of the solid electrolyte, which not only affects the transmission of lithium ions and has a large interface impedance, but also causes a gel jelly phenomenon when used with polyvinylidene fluoride (PVDF); thirdly, because the distribution of elements in the solid electrolyte is not completely uniform, there will be a gradient difference of lithium ions, and there will be Li on the surface of the solid electrolyte particles in the slurry. + / H + Proton exchange reaction, and by adding lithium-containing salt to the solid electrolyte slurry, the concentration of lithium ions in the solid electrolyte slurry can be increased and the Li + / H + Proton exchange reaction further improves the stability of the solid electrolyte slurry.

[0057] Therefore, the solid electrolyte slurry product obtained by the method has good storage stability, and as a slurry product, it can meet the requirements for stability during transportation, storage and use. At the same time, it also effectively prolongs the storage time of the product.

[0058] In order to better understand the technical solution provided by the present invention, the following uses a plurality of specific examples to illustrate the specific process of obtaining a solid electrolyte slurry product using the method provided by the present invention, and compares the proportions to illustrate the characteristics of the solid electrolyte slurry product obtained by the method of the present invention.

[0059] Example 1

[0060] After solid phase sintering, Li 1.4 Al 0.4 Ti 1.6 (PO4)3 is successively crushed by jaw crusher, roller and air flow crusher to obtain a micron-sized product of 3-10um. The micron-sized product and water are stirred and mixed at a mass ratio of 2:8, and introduced into a sand mill circulation tank for cyclic sand milling and nano-crushing. When the particle size reaches 50-100nm, a nano-sized product is obtained. 0.1mol / L LiPO2F2 is added under continuous stirring to obtain a slurry product A.

[0061] Comparative Example 1

[0062] After solid phase sintering, Li 1.4 Al 0.4 Ti 1.6 (PO4)3 is successively crushed by jaw crusher, roller and air flow to obtain a micron-sized product of 3-10um. The micron-sized product and water are stirred and mixed evenly at a mass ratio of 2:8, and introduced into a sand mill circulation tank for cyclic sand milling and nano-crushing. When the particle size reaches 50-100nm, nano-sized slurry D is obtained.

[0063] Example 2

[0064] The solid phase sintered Li7La3Zr2O 12 The particles are crushed by jaw crusher, roller and air flow mill in sequence to obtain a micron-sized product of 3-10 um. The micron-sized product and N-methylpyrrolidone containing trace water at the ppm level are stirred and evenly mixed in a mass ratio of 1:9. 0.5 mol / L LiBF4 is added under continuous stirring, and the mixture is introduced into a sand mill circulation tank for cyclic sand milling and nano-crushing. When the particle size reaches 200-300 nm, a slurry product B is obtained.

[0065] Comparative Example 2

[0066] The solid phase sintered Li7La3Zr2O 12 The particles are crushed by jaw crusher, roller crusher and air flow crusher in sequence to obtain a micron-sized product of 3-10 um. The micron-sized product and N-methylpyrrolidone containing trace water at the ppm level are stirred and mixed evenly in a mass ratio of 1:9, and introduced into a sand mill circulation tank for cyclic sand milling and nano-crushing. When the particle size reaches 200-300nm, slurry E is obtained.

[0067] Example 3

[0068] After solid phase sintering, Li 0.30 La 0.567 TiO3 is successively crushed by jaw crusher, roller crusher and air flow crusher to obtain a micron-sized product of 3-10um. The micron-sized product and ethanol containing trace water at ppm level are stirred and mixed evenly in a mass ratio of 2:8, and introduced into a sand mill circulation tank for cyclic sand milling and nano-reduction. 1 mol / L LiPF6 is added during the cyclic sand milling process. When the particle size reaches 100-200nm, a slurry product C is obtained.

[0069] Comparative Example 3

[0070] After solid phase sintering, Li 0.30 La 0.567 TiO3 is successively crushed by jaw crusher, roller crusher and air flow crusher to obtain a micron-sized product of 3-10um. The micron-sized product and ethanol containing trace water at ppm level are stirred and mixed evenly in a mass ratio of 2:8, and introduced into a sand mill circulation tank for cyclic sand milling and nano-crushing. When the particle size reaches 100-200nm, slurry F is obtained.

[0071] The pH value and sedimentation test were performed on the slurries of Examples 1-3 and Comparative Examples 1-3. The results are shown in Table 1.

[0072] Group pH Storage 30 days sedimentation state Storage 60 days sedimentation state Example 1 7 No subsidence No subsidence Comparative Example 1 8 No subsidence Slightly settled Example 2 8 No subsidence Slightly settled Comparative Example 2 12 Obvious settlement Layering Example 3 8 No subsidence No subsidence Comparative Example 3 13 Slightly settled Layering

[0073] Table 1

[0074] From the above comparison, it can be seen that, for the same solid electrolyte material and solvent, the product of the present invention has a lower pH value and better anti-sedimentation properties when the lithium-containing salt is added to the slurry product using the method of the present invention compared with the control example in which the lithium-containing salt is not added.

[0075] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for improving the stability of a solid electrolyte slurry product, characterized in that: The method comprises: adding the lithium-containing salt when the solid electrolyte particles are mixed with the solvent, and performing cyclic sand milling and nano-processing in a sand mill circulation tank to obtain a solid electrolyte slurry product; Alternatively, the solid electrolyte particles and the solvent are mixed in proportion, cyclically sand-milled and nano-sized in a sand mill circulation tank, and the lithium-containing salt is added during the cyclic sand-milling process to obtain a solid electrolyte slurry product; Alternatively, the solid electrolyte particles and the solvent are mixed in proportion, and cyclically sand-milled and nano-milled in a sand mill circulation tank, and when the particle size of the solid electrolyte particles reaches a set size range, a solid electrolyte slurry is obtained; the lithium-containing salt is added to the solid electrolyte slurry under the condition of continuous stirring to obtain a solid electrolyte slurry product; The lithium-containing salt is added to the slurry product as an electrolyte dispersant to change the isoelectric point of the solid electrolyte powder particles in the solid electrolyte slurry product, so that the zeta potential of the dispersion system deviates from the potential near the isoelectric point of the powder itself, so that the electrostatic repulsion between the powder particles is greater than the van der Waals attraction, thereby stably dispersing in the solid electrolyte slurry; The solid electrolyte slurry comprises a solid electrolyte and a solvent; the solvent is water or a non-aqueous solvent containing trace amounts of water; Under the condition that the solvent is water, the lithium-containing salt and water generate a trace amount of acid to reduce or remove the residual alkali on the surface of the solid electrolyte and lower the pH value of the solid electrolyte slurry; or, Under the condition that the solvent is a non-aqueous solvent with trace water, the lithium-containing salt and the trace water generate trace acid to reduce or remove the residual alkali on the surface of the solid electrolyte and lower the pH value of the solid electrolyte slurry.

2. The method according to claim 1, characterized in that The lithium-containing salt added to the solid electrolyte slurry is used to increase the concentration of lithium ions in the solid electrolyte slurry and reduce the Li + / H + Proton exchange reaction improves the stability of solid electrolyte slurry.

3. The method according to claim 1, characterized in that The solid electrolyte comprises: NASICON-type oxide solid electrolyte Li 1+x A x B 2-x (PO4)3; wherein A is one or more of Al, La, In, Cr, Ga, Fe, Sc, Lu or Y; B is one or more of Ti, Ge, Zr, Hf or Sn; 0≤x≤0.5; or, Garnet-type oxide solid electrolyte Li x A3B2O 12 ; wherein A is one or more of La, Nb, Mg, Ba, Ca or Sr, B is one or more of Te, Ta, Nb, Zr or In, 0<x≤7; or, Perovskite-type oxide solid-state electrolysis of Li 3x La 2 / 3-x TiO3, 0<x≤2 / 3; or Anti-perovskite oxide solid electrolyte Li3OX, Li 3-2x A x BO, Li 1.9 OHCl 0.9 or Li2OHCl; wherein X is Cl and / or Br; A is Mg 2+ , Ca 2+ , Sr 2+ Or Ba 2+ One or more of, B is Cl and / or I, 0≤x<3 / 2; or, A halide solid electrolyte A3MX6; wherein A is at least one of Li or Na, M is at least one of trivalent metals In, Y, Er, Sc, and Zr, and X is at least one of Cl, Br, and I; The non-aqueous solvent includes: N-methylpyrrolidone, methanol, ethanol, acetone, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, C n H 2n+2 , C n H 2n , one or more of petroleum ether, cyclohexane, carbon tetrachloride, trichloroethylene, carbon disulfide, toluene, benzene, dichloromethane, chloroform, ether, ethyl acetate, and acetone; wherein 5≤n≤12; The lithium-containing salt includes: lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium difluorophosphate, lithium dioxalate borate, lithium difluorooxalate borate, bis(trifluoromethylsulfonyl imide) lithium, bis(fluorosulfonyl imide) lithium, difluorodioxalate lithium phosphate, lithium trifluoromethylsulfonate, (fluorosulfonyl) (perfluorobutylsulfonyl) imide lithium, bis(pentafluoroethylsulfonyl) imide lithium, bis(fluoromalonate) borate lithium, bis(2-methyl-2-fluoromalonate) borate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, lithium citrate, lithium acetate, lithium oxalate, lithium acetate, lithium borate, lithium perchlorate, lithium chlorate, lithium nitrate, lithium iodate, lithium bromate, lithium hexafluorosilicate, lithium silicate, lithium sulfate or lithium phosphate.

4. The method according to claim 1, characterized in that: In the solid electrolyte slurry product, the content of lithium-containing salt is 0.01 mol / L-2.0 mol / L; the content of solid electrolyte is 1 wt%-80 wt%.

5. A solid electrolyte slurry product obtained by the method for improving the stability of a solid electrolyte slurry product according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Composite solid electrolyte and solid-stage battery

    CN107887639A

  • High ionic conductivity solid electrolyte and preparation method thereof as well as application of high ionic conductivity solid electrolyte in all-solid-state lithium ion battery

    CN108630985A

  • All-solid lithium ion battery with porous gradient structure and preparation method thereof

    CN110350238A

  • Solid-state battery and preparation method thereof

    CN111710851A

  • Method for improving discoloration and gelling of solid electrolyte, preparation method of solid electrolyte and solid electrolyte

    CN112768752A